(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article presents a comparative typological analysis of the syntactic features of subordinate phrases in Present Day English, Uzbek, and Russian. It examines structural differences and similarities, classification of subordinate clauses, word order tendencies, and functional-semantic roles of subordination. The paper also highlights examples from each language to illustrate key distinctions.